The Interplay Between Diabetes and Pancreatitis: Two Case Reports of Sudden, Natural Deaths and a Review of the Literature. Issue 2 (16th November 2016) - Butler, Daniel C.; Emanuel, Anthony J.; Self, Sally E.; Batalis, Nicholas I.
Abstract: Diabetes mellitus (DM) is a common disease involving insulin resistance or deficit that, when left unchecked, may cause severe hyperglycemia and subsequent end‐organ damage. Acute pancreatitis (AP) is inflammation of the pancreas that can lead to significant morbidity and mortality. AP and DM both account for a significant amount of sudden deaths, and rarely both disease processes may be present in the same decedent, causing some difficulty in wording the cause of death statement. Although much research has been directed at studying the causes and risk factors for AP and DM, there is a complex interplay between these diseases that is not fully understood. This study presents two autopsy cases of sudden, natural deaths that illustrate this interplay, along with a review of the literature. An algorithm for differentiating AP and DM is then discussed in the context of the presented cases as a proposed aid for forensic pathologists in the certification of such deaths.